2013
DOI: 10.3342/ceo.2013.6.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Analysis of Intraorbital Structures Regarding Sinus Surgery Using Multiplanar Reconstruction of Computed Tomography Scans

Abstract: ObjectivesThis study aimed to investigate the anatomy of the intraorbital structures regarding to endoscopic sinus surgery and external frontal sinus surgery analyzing computer tomography (CT) scans.MethodsThe CT scans of 100 patients were retrospectively evaluated. The anatomic relationships between the intraorbital structures and paranasal structures were measured using multiplanar reconstruction of the CT scan.ResultsThe mean distances from the medial orbital floor (MOF) to the intraorbital structures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…Note that the anterior part of the bony margin was not clearly visible in the MRI image; thus, we had to reconstruct it with information from other X-ray computed tomography images of healthy orbits (we used an anterior diameter of 35 mm). 17 Note also that the anterior portion of our 3D reconstructed eye geometry (anterior portion of the globe and fat) was simplified because we are not concerned with the stress/strain distributions in this area.…”
Section: D Digital Reconstruction Of the Human Eye And Orbitmentioning
confidence: 99%
“…Note that the anterior part of the bony margin was not clearly visible in the MRI image; thus, we had to reconstruct it with information from other X-ray computed tomography images of healthy orbits (we used an anterior diameter of 35 mm). 17 Note also that the anterior portion of our 3D reconstructed eye geometry (anterior portion of the globe and fat) was simplified because we are not concerned with the stress/strain distributions in this area.…”
Section: D Digital Reconstruction Of the Human Eye And Orbitmentioning
confidence: 99%
“…They found that the mean distance between the medial orbital floor and the inferior margin of the MRM was 7.3 mm measured at the anterior ethmoid and 2.9 mm at the posterior ethmoid. According to several publications, 15,16 the mean distance between the inferior and superior margins of the MRM lies between 7.2 and 9 mm. Karaki et al 17 suggest that the location of the basal lamella of the middle turbinate (third lamella) is the most important landmark for an endoscopic endonasal approach to the orbital retrobulbar space.…”
Section: Muscle Structuresmentioning
confidence: 99%
“…There are several landmarks that can be useful to open this surgical corridor safely. Hwang et al 15 analyzed the orbit and paranasal sinuses of 100 patients by computed tomographic scan. They found that the mean distance between the medial orbital floor and the inferior margin of the MRM was 7.3 mm measured at the anterior ethmoid and 2.9 mm at the posterior ethmoid.…”
Section: Muscle Structuresmentioning
confidence: 99%
“…Aksiyel ve sagittal kesitlerde frontal sinüsün değerlendirilmesi cerrahi sırasında ortaya çıkabilecek kanamaları ve komşu doku yaralanmalarını en aza indirebilir. 12 Literatürde frontal sinüse uygulanacak ESC sonrası epistaksis, orbital ekimoz, amfizem, diş ağ-rısı, adezyon gelişimi ve frontal ostiumda stenoz gelişimi gibi minör komplikasyonlar ve BOS fistülü, intraorbital hemoraji, körlük, menenjit, beyin absesi, anozmi ve ciddi epistaksis benzeri majör komplikasyonlar bildirilmiştir. [13][14][15] Çalışmamızda bir hastada (%5) postoperatif tampon uygulaması gerektiren epistaksis ve 2 hastada frontal sinus ostiumunda stenoz (%10) gelişti.…”
Section: Tanıunclassified